Uncommon secondary metabolites from Etlingera pavieana rhizomes - Sirichan Tachai (2018)
© 2016 Informa UK Limited, trading as Taylor & Francis Group. From the rhizomes of Etlingera pavieana (Pierre ex Gagnep.) R.M. Sm., four phenylpropens, (E)-3-(4-methoxyphenyl)prop-2-en-1-amine (1), (E)-4-methoxycinamaldehyde (2), (E)-4-methoxycinamic acid (3) and (E)-1-methoxy-4-(3-methoxyprop-1-enyl)benzene (4), together with two other compounds, (E)-((E)-3-(4-methoxyphenyl)allyl)3-(4-hydroxyphenyl)acrylate (5) and 4-methoxybenzoic acid (6) were isolated. This is the first report on the presence of all compounds in Etlingera. Compounds 1 and 5 have been previously synthesised, but this is the first report of their isolation from a natural source. Compound 5 exhibited weak activity against Mycobacterium tuberculosis with MIC 50.00 μg/mL and cytotoxic activity against the KB, MCF7 and NCI-H187 cells with IC50values of 25.11, 20.16 and 34.83 μg/mL, respectively.